Answer:
[tex]a_{i} = \frac{(-3)^{i}}{4\cdot i!}[/tex] converges.
Step-by-step explanation:
The convergence analysis of this sequence is done by Ratio Test. That is to say:
[tex]r = \frac{a_{n+1}}{a_{n}}[/tex], where sequence converges if and only if [tex]|r| < 1[/tex].
Let be [tex]a_{i} = \frac{(-3)^{i}}{4\cdot i!}[/tex], the ratio for the expression is:
[tex]r =-\frac{3}{n+1}[/tex]
[tex]|r| = \frac{3}{n+1}[/tex]
Inasmuch [tex]n[/tex] becomes bigger, then [tex]r \longrightarrow 0[/tex]. Hence, [tex]a_{i} = \frac{(-3)^{i}}{4\cdot i!}[/tex] converges.